Hyaluronan-decorated polymer nanoparticles targeting the CD44 receptor for the combined photo/chemo-therapy of cancer. Issue 13 (4th February 2015) - Maiolino, Sara; Moret, Francesca; Conte, Claudia; Fraix, Aurore; Tirino, Pasquale; Ungaro, Francesca; Sortino, Salvatore; Reddi, Elena; Quaglia, Fabiana
Abstract : CD44-targeted hyaluronan-decorated double-coated nanoparticles delivering the lipophilic chemotherapeutic docetaxel and an anionic porphyrin are developed and tested in human breast cancer cells. Abstract : In the attempt to develop novel concepts in designing targeted nanoparticles for combination therapy of cancer, we propose here CD44-targeted hyaluronan-decorated double-coated nanoparticles (dcNPs) delivering the lipophilic chemotherapeutic docetaxel (DTX) and an anionic porphyrin (TPPS4 ). dcNPs are based on electrostatic interactions between a negative DTX-loaded nanoscaffold of poly(lactide- co -glycolide), a polycationic shell of polyethyleneimine entangling negatively-charged TPPS4 and finally decorated with hyaluronan (HA) to promote internalization through CD44 receptor-mediated endocytosis. DTX/TPPS4 -dcNPs, prepared through layer-by-layer deposition, showed a hydrodynamic diameter of around 180 nm, negative zeta potential and efficient loading of both DTX and TPPS4 . DTX/TPPS4 -dcNPs were freeze-dried with trehalose giving a powder that could be easily dispersed in different media. Excellent stability of dcNPs in specific salt- and protein-containing media was found. Spectroscopic behavior of DTX/TPPS4 -dcNPs demonstrated a face-to-face arrangement of the TPPS4 units in non-photoresponsive H-type aggregates accounting for an extensive aggregation of the porphyrin embedded in the shell. Experiments in MDA-MB-231 cells overexpressing the CD44 receptor demonstrated a 9.4-fold increase in the intracellular level of TPPS4 delivered from dcNPs as compared to free TPPS4 . Light-induced death increased tremendously in cells that had been treated with a combination of TPPS4 and DTX delivered through dcNPs as compared with free drugs, presumably due to efficient uptake and co-localization inside the cells. In perspective, the strategy proposed here to target synergistic drug combinations through HA-decorated nanoparticles seems very attractive to improve the specificity and efficacy of cancer treatment.